Coefficient Bounds for Certain Subclasses of Analytic Functions Defined by Komatu Integral Operator - Serap Bulut (International Journal of Mathematics and Mathematical Sciences)
We determine the coeffcient bounds for functions in certain subclasses of analytic functions of complex order, which are introduced here by means of a certain non-homogeneous Cauchy–Euler type differential equation of order m. Relevant connections of some of the results obtained with those in earlier works are also provided.